ANALISIS YURIDIS PENYELESAIAN SENGKETA PEMILU SEBAGAI INSTRUMEN PENEGAKKAN HUKUM PEMILU DI INDONESIA - Diwan Pramulya; Cecep Cahya Supena (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
General elections constitute the primary mechanism for exercising popular sovereignty in a democratic state governed by the rule of law, as mandated by the 1945 Constitution of the Republic of Indonesia. In practice, however, the electoral process is frequently accompanied by various electoral disputes that may undermine the legitimacy of election outcomes, legal certainty, and public trust in democratic institutions. This study aims to examine electoral dispute resolution as an instrument of electoral law enforcement and to evaluate the effectiveness of the existing dispute resolution mechanisms in promoting legal certainty, justice, and electoral integrity in Indonesia. This research employs a normative legal research method using statutory, conceptual, and case approaches. The data were collected through library research, including legislation, judicial decisions, official reports, and relevant scholarly literature. The findings indicate that Indonesia's electoral dispute resolution system distributes authority among the General Election Supervisory Agency (Bawaslu), the Honorary Council of Election Organizers (DKPP), the State Administrative Court, the Supreme Court, and the Constitutional Court. Nevertheless, its implementation continues to face significant challenges, including regulatory inconsistencies, overlapping institutional jurisdictions, and insufficient inter-agency coordination, which collectively hinder the effectiveness of electoral law enforcement. The novelty of this research lies in proposing the Integrated Electoral Dispute Resolution System (IEDRS) as a conceptual framework for harmonizing electoral dispute resolution through regulatory integration, institutional coordination, and effective implementation of judicial decisions to strengthen legal certainty, enhance electoral law enforcement, and improve the quality of democracy in Indonesia.